Identification of inelastic parameters of the 304 stainless steel using multi-objective techniques - Vaz M.* (2017)
© 2017 International Center for Numerical Methods in Engineering. All rights reserved.This work addresses identification of inelastic parameters based on an optimization method using a multi-objective technique. The problem consists in determining the best set of parameters which approximate three different tensile tests. The tensile tests use cylindrical specimens of different dimensions manufactured according to the American ASTM E 8M and Brazilian ABNT NBR ISO 6892 technical standards. A tensile load is applied up to macroscopic failure. The objective functions for each tensile test/specimen is computed and a global error measure is determined within the optimization scheme. The Nelder-Mead simplex algorithm is used as the optimization tool. The proposed identification strategy was able to determine the best set of material parameters which approximate all tensile tests up to macroscopic failure.